Business Collaboration Meets Social Collaboration : Building a Community for SharePoint Users - Munoz, Javier (World Bank, Washington, DC, 2012)
New communication technologies are changing the way World Bank Group (WBG) staff work and interact with their colleagues. For example, teams in different locations and time zones can use virtual collaboration platforms for communication and knowledge management. During 2009 and 2010, the Latin America and Caribbean (LAC) and Poverty Reduction and Economic Management (PREM) units volunteered to participate in the pilot phase of the rollout of SharePoint, a common work space for teams that bundles a number of functions previously available only as separate applications. At the same time, there was an increase in demand across the WBG for a Facebook-type collaboration platform, called 'Scoop,' which responded to teams' need for a virtual platform to support social collaboration. SharePoint had already exceeded expectations, with many staff members from different units in the WBG headquarters and country offices becoming active users, and the number of site requests increasing weekly. This demand brought the need to identify and group all SharePoint site owners and users so everyone could connect, share and learn from each other. This smart lesson describes how one of the so-called 'SharePoint evangelists' came to create a group in scoop, which quickly started attracting members from all corners of the WBG.